Investigating the potential for ethnic group harm in collaborative genomics research in Africa: Is ethnic stigmatisation likely? - de Vries, J; de Vries, J; Jallow, M; Williams, T; Kwiatkowski, D; Kwiatkowski, D; Parker, M; Fitzpatrick, R (2012)
A common assumption in genomics research is that the use of ethnic categories has the potential to lead to ethnic stigmatisation - particularly when the research is done on minority populations. Yet few empirical studies have sought to investigate the relation between genomics and stigma, and fewer still with a focus on Africa. In this paper, we investigate the potential for genomics research to lead to harms to ethnic groups. We carried out 49 semi-structured, open-ended interviews with stakeholders in a current medical genomics research project in Africa, MalariaGEN. Interviews were conducted with MalariaGEN researchers, fieldworkers, members of three ethics committees who reviewed MalariaGEN project proposals, and with members of the two funding bodies providing support to the MalariaGEN project. Interviews were conducted in Kenya, The Gambia and the UK between June 2008 and October 2009. They covered a range of aspects relating to the use of ethnicity in the genomics project, including views on adverse effects of the inclusion of ethnicity in such research. Drawing on the empirical data, we argue that the risk of harm to ethnic groups is likely to be more acute in specific types of genomics research. We develop a typology of research questions and projects that carry a greater risk of harm to the populations included in genomics research. We conclude that the potential of generating harm to ethnic groups in genomics research is present if research includes populations that are already stigmatised or discriminated against, or where the research investigates questions with particular normative implications. We identify a clear need for genomics researchers to take account of the social context of the work they are proposing to do, including understanding the local realities and relations between ethnic groups, and whether diseases are already stigmatised. © 2012 Elsevier Ltd.